Effect of Temperature on Physical Characteristics of Nickel Electrodeposited from Nickel Salts in Presence 1,4-Dioxane-aqueous Bath - SRIVASTAV, H.K.; PANDEY, AARTI (Asian Journal of Chemistry, 2010)
Electrodeposition of metal or its alloy not only protects the base metal but also provide decorative appeal. Nickel is one of the most important metals employed for electrodeposition on various base metals. There are various parameters, which affect the physical characteristics of nickel electrodeposited from different salt solutions. Temperature is one such parameter whose effect on physical characteristics (cathode current efficiency and thickness) of the nickel electrodeposited from nickel acetate alone or in combination with nickel formate and nickel sulphamete in presence of 0, 10 and 20 mol % 1,4-dioxane has been observed. It has been found out that variation in temperature affects the values of cathode current efficiency and thickness.